2021
DOI: 10.47689/2181-1415-vol2-iss2/s-pp76-90
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of women leaders with intellectual potential in human resources management

Abstract: The purpose of this research is to assess the impact of women leaders in human resource management. Women leaders with intellectual potential were selected as focus of the research and accordingly women leadership characteristics as independent variable and HRM processes as dependent variable were chosen. This topic is relevance because of women leaders have characteristics which able to manage successfully of human resource processes. The design of this research is qualitative, its type is explanatory researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The study suggests women executives need more support to do better. Fayzieva & Ganieva (2021) explored how female entrepreneurship affects business performance. The study of more than 50 SMEs indicated that organizations with female leaders were more efficient, resourceful, and innovative.…”
Section: Female Entrepreneursmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggests women executives need more support to do better. Fayzieva & Ganieva (2021) explored how female entrepreneurship affects business performance. The study of more than 50 SMEs indicated that organizations with female leaders were more efficient, resourceful, and innovative.…”
Section: Female Entrepreneursmentioning
confidence: 99%
“…Academics have recently studied female corporate executives' leadership styles and team innovation. Fayzieva and Ganieva (2021) found that female entrepreneurs' more focused and collaborative leadership style inspires team members' inventiveness. Female entrepreneurs' leadership styles emphasize staff skill development, which can inspire innovation, according to Laily et al (2020).…”
Section: Introductionmentioning
confidence: 99%